Pseudoangiosarcomatous carcinoma of the genitourinary tract. Issue 11 (November 1995) - Pitt, M A; Morphopoulos, G; Wells, S; Bisset, D L
Abstract : Two cases of pseudoangiosarcomatous carcinoma of the genitourinary tract, arising in the vulva in one and the bladder in the other, are presented. In case 1, an 84 year old woman, the vulvectomy specimen contained an irregular ulcerated tumour, infiltrating the left labia and extending into the clitoris. In case 2, a 59 year old woman, the excised bladder showed diffuse thickening of its wall by infiltrating haemorrhagic tumour. Both tumours showed focal keratinisation. This, in association with the presence of atypical squamous epithelium, immunohistochemistry and ultrastructural analysis, led to a diagnosis of pseudosarcomatous carcinoma in both cases. Pseudoangiosarcomatous carcinoma should be considered in the differential diagnosis of malignant angiomatoid tumours, particularly those that arise at sites, like the genitourinary tract, where angiosarcoma is rare.